Placement and sizing evaluation of distributed generation in electric power systems - Lopez Lezama, Jesus Maria [UNESP]; Padilha Feltrin, Antonio [UNESP] (Institution of Engineering and Technology (IET), 2009)
This paper presents a methodology for the placement and sizing evaluation of distributed generation (DG) in electric power systems. The candidate locations for DG placement are identified on the bases of Locational Marginal Prices (LMP's) obtained from an optimal power flow solution. The problem is formulated for two different objectives: social welfare maximization and profit maximization. For each DG unit an optimal placement is identified for each of the objectives.
Keywords: Candidate locations; DG unit; Distributed Generation; Distributed generations; Locational marginal prices; Optimal placements; Optimal power flows; Profit maximization; Social welfare maximization; Distributed power generation; Electric power distribution; Electric power measurement; Electric power transmission networks; Electric utilities; Galerkin methods; Optimization; Power electronics; Profitability; Electric generators